Urban and Social Regeneration in Abruzzo: An Open Problem and a Possible Way Forward - Veraldi, Roberto; Carballar, Sandra (European Scientific Journal, ESJ, 2022)
Urban and social regeneration occurs through the recovery of disused built-up areas, requalifying them with respect to environmental sustainability and the recovery of the relational relationship between social actors. In the last few years, the practices of sociourban regeneration have made great strides, establishing themselves as an opportunity to promote policies of social participation, stimulating employment, and local entrepreneurship. Sociourban regeneration can thus be defined as a set of actions that focuses on the recovery of sociality and the requalification of an urban space. The regeneration process takes place by means of rehabilitation interventions at the level of infrastructures and services, thereby limiting the consumption of land in order to protect environmental sustainability. Regeneration also allows the community to re-appropriate and re-live the regenerated spaces with clear improvements in the quality of life and in the social, economic, and environmental spheres. This paper focuses on exploring the relationship between urban and social regeneration and economic growth in Abruzzo (Italy) by using a set of indicators that measures equitable and sutainable welldoing (Bes). A descriptive analytical method was adopted to evaluate the level of urban quality in order to identify the most appropriate interventions leading to sustainable local development. The main finding indicates that Abruzzo shows interesting potential, but it has yet a long way to go in the area of urban and social regeneration.